PENGEMBANGAN MEDIA PEMBELAJARAN PERMAINAN MONOPOLI BERBASIS KEARIFAN LOKAL PADA MATERI NORMA DALAM ADAT ISTIADAT KELAS IV SD MUHAMMADIYAH 1 PURWOREJO - Desy Permata Hati; Arum Ratnaningsih; Titi Anjarini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to develop learning media in the form of a monopoly game as a learning media that is feasible and according to the needs of students on the material of norms in customs of class IV SD Muhammadiyah 1 Purworejo. The research design used is a research and development or R&D model with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Data collection techniques include observation, interviews, questionnaires, tests, and documentation. The subjects of this research were fourth grade students of SD Muhammadiyah 1 Purworejo, totaling 15 students. This research produced a learning media monopoly game based on local wisdom on the material of norms in customs of grade IV SD Muhammadiyah 1 Purworejo. Based on the feasibility aspect, the lecturer validation obtained an average score of 3.4 with a very feasible category. The practicality aspect is done by the teacher getting an average score of 4 with a very practical category. While based on student responses, the limited trial with an average score of 3.6 with a very practical category and a broad trial with an average score of 3.5 with a very practical category. The effectiveness aspect of the monopoly game learning media can be seen from the completeness of student learning outcomes in the limited test getting a score of 0.58 with a medium category and the broad trial getting a score of 0.67 with a medium category, so it can be concluded that the monopoly game learning media can be declared feasible.